Explaining Liberalization Commitments in Financial Services Trade - Harms, Philipp (World Bank, Washington, DC, 2014)
The authors examine the determinants of market access commitments in international financial services trade in the General Agreement on Trade in Services (GATS). Based on a theoretical model, they investigate empirically the role of domestic political economy forces, international bargaining considerations, and the state of complementary policy. The empirical results confirm the relevance of the authors' model in explaining banking and (to a somewhat lesser degree) securities services liberalization commitments. The findings imply that those who seek greater access to developing country markets for financial services must do more to counter protectionism at home in areas of export interest for developing countries.